Specific muscle-tendon architecture in elite Kenyan distance runners - Kunimasa, Y.; Sano, K.; Oda, T.; Nicol, C.; Komi, P. V.; Locatelli, E.; Ito, A.; Ishikawa, M. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The Achilles tendon moment arm (MA_AT) and foot lever ratio (FLR) can play important roles for force production and movement economy during locomotion. This notion has become more relevant, and suggestion has been given that the Kenyan runners belonging to the world elite would have specific anatomical, mechanical, and functional properties in their lower limbs and that this feature could be responsible for their high running economy. The present study aimed to characterize the AT of elite Kenyan distance runners as compared with Japanese ones, and to examine the potential relationship with their running performance. Ultrasonography was used to measure AT cross-sectional area and AT soleus and gastrocnemius lengths. MA_AT and FLR were calculated from the position of anatomical landmarks using sagittal plane photographs. MA_AT was significantly longer and the FLR lower in Kenyans than in Japanese. Independently of the group, the running performance was positively related to the MA_AT (r = 0.55, P < 0.001) and negatively to the FLR (r = -0.45, P = 0.002). These results suggest that longer MA_AT and lower FLR could be advantageous in elite Kenyan runners, by contributing to effective endurance running performance in a protective and economical way.